Folic Acid-Coated Nanochitosan Ameliorated the Growth Performance, Hematological Parameters, Antioxidant Status, and Immune Responses of Rainbow Trout (Oncorhynchus mykiss) - Farahnak Roudsari, Sahar; Rajabi Islami, Houman; Mousavi, Seyed Abdolmajid; Shamsaie Mehrgan, Mehdi (Frontiers in Veterinary Science, 2021)
In recent years, chitosan has gained considerable attentions due to its well-documented properties including extended biocompatibility and biodegradability which can be used as health Supplement for delivering bioactive compounds in food industry and nutrition. In the present study, the effects of FA coated nanochitosans on growth performance, hematological parameters, antioxidant status, and serum immune responses of rainbow trout (Oncorhynchus mykiss) fingerlings were studied. Graded levels of FA coated nanochitosan )0, 0.1, 0.25, 0.5 and 1 mg kg-1 diet) were added to the basal diet. Each experimental diet was fed to three groups of fish with approximate weight of 31 g for 8 weeks. In comparison to the control diet, dietary FA coated nanochitosan significantly (P<0.05) improved weight gain ration (WGR), specific growth rate (SGR), feed conversion ratio (FCR) of fish at the end of feeding trial. There were also linear increasing trends in red blood cells (RBCs), white blood cells (WBCs), hemoglobin (Hb), and hematocrit (Hct) of fish with increasing dietary chitosan/FA level, whereas no significant difference was recorded in differential leukocytes count. In case of antioxidant responses, fish fed diet supplemented with 0.50 mg kg-1 FA coated nanochitosan had the highest CAT and SOD activities, while the maximum activity of GPX was found in fish fed the 1.00 mg kg-1 FA coated nanochitosan supplemented diet. Malondialdehyde activity was also reached to lowest value in fish fed with 1.00 mg kg-1 FA coated nanochitosan supplemented diet (P<0.05). Measured immune responses including showed a linear augmentation in lysozyme activity (LA) of fish with increasing dietary FA coated nanochitosan, while linearly and quadratically increasing trend in IgM content followed by the C3 and C4 activities were recorded as the dietary FA coated nanochitosan supplementation increased and reached to their peaks in fish fed the diet supplemented with 0.50 mg kg-1 FA coated nanochitosan (P<0.05). Findings of the current study illustrated the positive effect of dietary FA coated nanochitosan as a promising compound on improving growth performance, feed utilization and antioxidant status, immune responses of rainbow trout.